Prompt and non-prompt J/Psi production cross sections at midrapidity in proton-proton collisions at √s = 5.02 and 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Kroesen, Martin; et al. (Journal of high energy physics, 2022)
The production of J/ψ is measured at midrapidity (|y| < 0.9) in proton-proton collisions at $$ \sqrt{s} $$= 5.02 and 13 TeV, through the dielectron decay channel, using the ALICE detector at the Large Hadron Collider. The data sets used for the analyses correspond to integrated luminosities of $$ \mathcal{L} $$int = 19.4 ± 0.4 nb−1 and $$ \mathcal{L} $$int = 32.2 ± 0.5 nb−1 at $$ \sqrt{s} $$= 5.02 and 13 TeV, respectively. The fraction of non-prompt J/ψ mesons, i.e. those originating from the decay of beauty hadrons, is measured down to a transverse momentum pT = 2 GeV/c (1 GeV/c) at $$ \sqrt{s} $$= 5.02 TeV (13 TeV). The pT and rapidity (y) differential cross sections, as well as the corresponding values integrated over pT and y, are carried out separately for prompt and non-prompt J/ψ mesons. The results are compared with measurements from other experiments and theoretical calculations based on quantum chromodynamics (QCD). The shapes of the pT and y distributions of beauty quarks predicted by state-of-the-art perturbative QCD models are used to extrapolate an estimate of the $$ b\overline{b} $$pair cross section at midrapidity and in the total phase space. The total $$ b\overline{b} $$cross sections are found to be $$ σ_{b\overline{b}} $$= 541 ± 45 (stat.) ± 69 $$ {\left(syst.\right)}_{-12}^{+10} $$(extr.) μb and $$ σ_{b\overline{b}} $$= 218±37 (stat.)±31 $$ {\left(syst.\right)}_{-9.1}^{+8.2} $$(extr.) μb at $$ \sqrt{s} $$= 13 and 5.02 TeV, respectively. The value obtained from the combination of ALICE and LHCb measurements in pp collisions at $$ \sqrt{s} $$= 13 TeV is also provided.